Analisis Efisiensi dan Efektivitas Penerimaan Retribusi Pasar dalam Upaya Peningkatan Pendapatan Asli Daerah di Kabupaten Hulu Sungai Tengah Tahun 2014-2019 - Fitri , Ainun; Syafrudin , Ruddy (JIEP: Jurnal Ilmu Ekonomi dan Pembangunan, 2021)
Market retribution has the potential to increase its revenue and there needs to be strategic and sustainable efforts so that local revenue will increase and the benefits will be felt for the whole community. This research is a descriptive study with a quantitative approach whose data sources are obtained from interviews and reports such as the realization of local revenue, the realization of local fees, the target and realization of wholesale / shopping market levies and reports on the costs of collecting wholesale / shopping market levies from 2014-2019. The data analysis technique uses contribution analysis, efficiency analysis, effectiveness analysis and projection analysis The result of the research shows that the contribution of market retribution to regional levies in Hulu Sungai Tengah regency as a whole is classified as insignificant. The overall efficiency level is classified as very efficient, but only 1 year is not classified as inefficient. The effectiveness level of wholesale / shopping market levies has fluctuated. The projection analysis of market retribution receipts for 2020 produces an average percentage of -5% because it uses a pessimistic assumption with a reference to an average economic growth of -5%, in 2021 it is 0% because it uses the muderat assumption based on an average economic growth of 0%. and the years 2022-20224 resulted in a percentage change, namely there is always an increase of 5.66% using the assumption of an optimistic scenario based on the average growth of market levies.